Artificial Intelligence in Islamic Philosophy: a Qur’anic Epistemological Framework for AI Ethics - Ahmad Baiquni; Ahmad Raihan Al Biruni; Juhardin (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2026)
This study examines the epistemological relationship between Artificial Intelligence (AI) and the values of the Qur’an, with the aim of formulating a model for the Islamization of AI within the framework of the Islamic worldview. This study constructs a normative-conceptual framework for the development of AI that aligns with the principles of tawhid, maqasid al-shari’ah, and Qur’anic ethics. This study employs a literature-based qualitative design with a philosophical-analytical approach. The findings indicate that, ontologically, AI is a neutral tool (mubah), where its ethical status depends on the worldview and intentions guiding its use. Epistemologically, the primary distinction between the secular paradigm and Islamic epistemology lies in the integration of revelation as a legitimate and authoritative source of knowledge, which shapes the value orientation in technological development. This study proposes a model for the Islamization of AI based on three Qur’anic principles: reason (‘aql), knowledge (‘ilm), and order (nazm). These principles emphasize the importance of accountable algorithmic governance, authoritative knowledge validation, and continuous human oversight. Practically, this model provides a foundational framework for the ethical use of AI, guiding Muslim scholars, technology experts, and policymakers in designing AI systems that align with Islamic ethical values